Comunidades sustentáveis: elementos de análise do desenvolvimento sustentável que representem simbiose entre rural e urbano para distritos municipais - Ferreira, Thayse Ana (2019)
Search for sustainable development in urban environments, the challenge is to measure the limitations and potential of cities, as their growth usually occurs without planning, what results in increased pollution and in a strong inequality in access to services basic. In rural areas there are also challenges for the effectiveness of sustainable development, since agricultural expansion is usually disorderly and aim practices that are very harmful to the environment. In the case of the municipal districts, there are spaces with agricultural establishments that are characterized as rural communities and the seat of the district, commonly called "village", is considered as an urban area. In this way, these communities present both rural and urban characteristics. The objective of this research was to propose elements for sustainable development analysis that represent symbiosis between rural and urban to municipal districts. Firstly, it was made a survey of indicators for sustainable urban and rural development and a comparative synthesis between several authors. Based on this analysis, it was possible to define the set of indicators focused specifically on these communities, later, the data collection was done through the application of a questionnaire and the accomplishment of two interviews, besides the analysis of the information of the district, made available by the IBGE, referring to the 2010 Census. Data analysis showed a general picture of the situation of sustainable development in the district, observing the governmental initiatives, the initiatives of the residents themselves, what their evaluation of the basic services of the district and how it is their behaviors and habits. Some of the residents practice sustainable behavior, but that there are people who do not yet have this awareness. Regarding the critical points, it was verified that in the studied district there are some related to the public power, such as the precariousness in the sewage treatment and in the police service, besides there is not Municipal Center for Early Childhood Education to attend the population of the district. There are still housing in high-risk areas, and residents are waiting transfer to an area of land-use regulation, what harms them as well as the environment. But there are also factors related to the behaviors of the residents, such as illegal hunting and burning. It is hoped that the research results will contribute to the elaboration of future public policies, such as creation of a police station, availability of CMEI vacancies, investment in the infrastructure for collection and treatment of sewage and establishment of environmental awareness projects. In addition to providing a methodology that can be replicated in the future, through the general outline presented in this work about the São João do Oeste municipal district, it contributes with the community, showing which aspects need to be changed in order to achieve sustainable development.